Opportunity crops for gender equality and women’s empowerment: Revisiting the narrative - Zaremba, Haley; Elias, Marlene (Bioversity International and International Center for Tropical Agriculture, 2025)
- Opportunity crops are often lauded for their potential to empower rural women and increase their livelihood opportunities, but these assertions have received little empirical attention. - Evidence shows that the relationship between opportunity crops and gender equality and women’s empowerment is nuanced and context-specific. - Narratives and interventions focused on opportunity crops should also take a nuanced and holistic approach to account for these contextual differences and complexities.